The Composition of Intestinal Microbiota From Collichthys lucidus and Its Interaction With Microbiota From Waters Along the Pearl River Estuary in China - Wu, Peng; Liu, Yong; Li, Chunhou; Xiao, Yayuan; Wang, Teng; Lin, Lin; Xie, Yufang (Frontiers in Environmental Science, 2021)
By their nature and geographical location, estuaries shape different marine habitats via freshwater and seawater interactions. Thus, fish intestinal microbiota, as mediated by estuary habitat fluctuations, are fundamentally important but rarely studied. Similarly, it is unclear how, and to what extent, water microbiota influences fish intestinal microbiota in different estuary habitats. In this study, the euryhaline fish species, Collichthys lucidus from three different habitats in the Pearl River estuary (PRE) was investigated to determine the influence of habitat fluctuation on intestinal microbiota. The three water environments selected for sample collection were very different, particularly for chlorophyll-a, suspended solid, and nutrient constituents. Using high-throughput sequencing of 16S rRNA gene amplicons, we observed that dominant microbial genera in surrounding estuary waters or fish intestines were seldom shared. The most dominant genera in water samples were Candidatus Actinomarina and HIMB11, while Bifidobacterium, Stenotrophomonas, Escherichia-Shigella and Rhodopseudomonas were more abundant in fish intestines. Fish hosts can shape fish intestinal microbiota. However, microbial exchange was also found between fish intestines and water samples. The frequency of microbial exchange between fish intestines and water samples was increased from upstream to downstream estuary points, and was influenced by changes in seawater salinity in the estuary. Finally, core intestinal microbiota from C. lucidus was analyzed, and showed that Bifidobacterium, Rhodopseudomonas, Escherichia-Shigella, Acinetobacter, and Stenotrophomonas were highly abundant. These microbiota were theoretically implicated in immune responses, nutrient metabolism, probiotics, and potential pathogen behaviors. Overall, these data highlighted the composition of C. lucidus intestinal microbiota in different habitats across the PRE.